Low velocity impact response of fibre metal laminates based on aramid fibre reinforced polypropylene. (15th July 2019) - Carrillo, J.G.; Gonzalez-Canche, N.G.; Flores-Johnson, E.A.; Cortes, P.
Abstract: In this work, the low velocity impact behaviour of thermoplastic fibre metal laminates (FMLs) made of aramid fibre reinforced polypropylene and aluminium alloy Al 5052-H32 is presented. The impact behaviour of these FMLs and their constituent materials was determined using a drop-weight impact tower. Force-time curves were used to obtain the absorbed energy for each tested material at different impact energies. The results showed that the FML configuration based on a 3/4 layering arrangement (3 layers of aluminium and 4 layers of composite) exhibited the highest specific absorbed energy for the first damage and perforation threshold when compared to the other laminates and constituent materials here studied. Optical analysis showed that the plastic deformation and the tearing of the aluminium layers, as well as fibre breakage and delamination were the main impact energy-absorption mechanisms. These findings warrant further research to fully understand the low velocity impact behaviour of these thermoplastic FMLs for engineering applications.